2012
DOI: 10.1177/0893318912458214
|View full text |Cite
|
Sign up to set email alerts
|

Between Rocks and Hard Places

Abstract: Recurrent interpersonal conflict in organizational settings is common and impedes goal-attainment. Structurational divergence (SD) theory conceptualizes a distinctive negative communication spiral rooted in unresolved conflict resulting from incompatible rules of intersecting meaning structures. This article expands SD theory by examining the function of human agency, positing that the rendering of communication patterns as incomprehensible and untransformable diminishes agency. After explaining and expanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 64 publications
(120 reference statements)
2
38
0
1
Order By: Relevance
“…The study determined that divergent structures of meaning contributed to conflict and miscommunication. Nicotera and Mahon (2013) suggested that future research focus on joint problem solving, stress management, and a dialogical approach (focus on dialogue) to handle conflict. Brinkert (2011) likewise proposed a dialogical approach with nurses in which narrative training helped nurses identify contributing factors and then suggested improved communication patterns based on dialogue.…”
Section: Medical Communication Trainingmentioning
confidence: 98%
See 1 more Smart Citation
“…The study determined that divergent structures of meaning contributed to conflict and miscommunication. Nicotera and Mahon (2013) suggested that future research focus on joint problem solving, stress management, and a dialogical approach (focus on dialogue) to handle conflict. Brinkert (2011) likewise proposed a dialogical approach with nurses in which narrative training helped nurses identify contributing factors and then suggested improved communication patterns based on dialogue.…”
Section: Medical Communication Trainingmentioning
confidence: 98%
“…Nicotera and Mahon (2013) used structurational divergence to examine contributing communication factors among nurses and other medical providers. The study determined that divergent structures of meaning contributed to conflict and miscommunication.…”
Section: Medical Communication Trainingmentioning
confidence: 99%
“…First, organizational cultures seemingly give rise to different perceptions of individual or organizational agency to address problems and enact solutions. Nicotera and Mahon (2012) argue, "agency arises from knowledge of structure; structures arise from agency (ability to act and to apply knowledge to new contexts; Sewell, 1992). So, when rules from multiple structures are irreconcilably incompatible, agency suffers" (p. 93).…”
Section: Three Theoretical Considerations Of Design In Addressing Wicmentioning
confidence: 99%
“…Conflict as an organizational phenomenon has been understood by communication scholars through an interpretive approach to the study of conflict and the constitutive relationship between communication and conflict (e.g., Brummans et al, 2008;Mease & Terry, 2012;Nicotera & Mahon, 2013). Influenced by Weick (1979), who was among the first to posit that communication is the means by which organizing occurs, conflict is not seen as static but comprised by inherently dynamic processes of communicating.…”
Section: Organizational Conflictmentioning
confidence: 99%
“…Influenced by Weick (1979), who was among the first to posit that communication is the means by which organizing occurs, conflict is not seen as static but comprised by inherently dynamic processes of communicating. Communication scholars such as Kusztal (2002), Putnam (2010), and Sheppard and Aquino (2013) take particular interest in the hegemonic and performative role of language and symbols in shaping and co-developing conflict, inspiring research into the discourses of conflict, while others (Brummans et al, 2008;Dewulf et al, 2009;Gray, 2003;Mikkelsen & Gray, 2016) focus on framing and issue development in conflict and language's constitutive effects on social interaction in conflict (Mease & Terry, 2012;Nicotera & Mahon, 2013;Putnam, Nicotera, & McPhee, 2009). From this interpretive approach to conflict, we learn that communication should not be seen as a variable affecting conflict outcomes but is a performative aspect of conflict (Putnam, 2013).…”
Section: Organizational Conflictmentioning
confidence: 99%